Les impasses critiques de la recherche participative : leçons tirées de débats épistémologiques en sociologie critique - Arianne Robichaud; Marina Schwimmer (Université de Provence, 2020)
The critical nature of participatory action research (PAR) is generally recognized amongst researchers in human and social sciences: by destabilizing the traditional relationships to knowledge and reformulating the hierarchies between experts and social actors, PAR is seen as an opportunity to develop the social actor's power in society as well as a way to legitimate the actor's knowledge and recognize his critical capacities. However, the critical foundations of PAR must be confronted to a reflection on its epistemological relation, in sociological terms, to the very notion of critique. Therefore, we examine in this paper three "critical problems" of PAR (the possibilities of 1- instrumentalizing the participants within PAR, 2- the question of the power relations between researchers and actors and 3- the dangers of an ideological recuperation of PAR's core principles by different organisations) in the light of certain debates in critical sociology that oppose a sociology of domination (Horkheimer, Adorno, Bourdieu) to a sociology of agency and communication (Boltanski, Habermas).